ANALYSIS AND FORECAST OF ELECTRIC CONSUMPTION IN THE ALTAI TERRITORY - A. Kurenkova; N. Lyubimova (Вестник университета)
Power consumption is one of the most important indicators of the region’s development. For the forecast of power consumption, the trend methods - econometric and normative - is usually used. Each of the methods has its drawbacks and peculiarities. In the article the forecast of power consumption of the economy and population of the Altai Territory is calculated by various methods. The most significant factors and their influence on the region’s energy consumption are determined: gross regional product, investment volume and industrial production index, population wages, electricity tariffs. A high degree of convergence of the results of forecasts is determined.